Honokiol inhibits signal transducer and activator of transcription-3 signaling, proliferation, and survival of hepatocellular carcinoma cells via the protein tyrosine phosphatase SHP-1 - Rajendran, P.; Li, F.; Shanmugam, M.; Vali, S.; Abbasi, T.; Kapoor, S.; Ahn, K.; Kumar, Alan Prem; Sethi, G. (John Wiley & Sons, Inc., 2012)
The activation of signal transducers and activators of transcription 3 (STAT3) has been closely linked with the proliferation, survival, invasion, and angiogenesis of hepatocellular carcinoma (HCC) and represents an attractive target for therapy. In the present report, we investigated whether honokiol mediates its effect through interference with the STAT3 activation pathway. The effect of honokiol on STAT3 activation, associated protein kinases, and phosphatase, STAT3-regulated gene products and apoptosis was investigated using both functional proteomics tumor pathway technology platform and different HCC cell lines. We found that honokiol inhibited both constitutive and inducible STAT3 activation in a dose- and time-dependent manner in HCC cells. The suppression was mediated through the inhibition of activation of upstream kinases c-Src, Janus-activated kinase 1, and Janus-activated kinase 2. Vanadate treatment reversed honokiol-induced down-regulation of STAT3, suggesting the involvement of a tyrosine phosphatase. Indeed, we found that honokiol induced the expression of tyrosine phosphatase SHP-1 that correlated with the down-regulation of constitutive STAT3 activation. Moreover, deletion of SHP-1 gene by siRNA abolished the ability of honokiol to inhibit STAT3 activation. The inhibition of STAT3 activation by honokiol led to the suppression of various gene products involved in proliferation, survival, and angiogenesis. Finally, honokiol inhibited proliferation and significantly potentiated the apoptotic effects of paclitaxel and doxorubicin in HCC cells. Overall, the results suggest that honokiol is a novel blocker of STAT3 activation and may have a great potential for the treatment of HCC and other cancers.